2022
DOI: 10.3390/molecules27051512
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal and Bacterial Content in a Two-Stage Anaerobic System for Efficient Energy Production from Agricultural Wastes

Abstract: Anaerobic digestion (AD) is a microbially-driven process enabling energy production. Microorganisms are the core of anaerobic digesters and play an important role in the succession of hydrolysis, acidogenesis, acetogenesis, and methanogenesis processes. The diversity of participating microbial communities can provide new information on digester performance for biomass valorization and biofuel production. In this study anaerobic systems were used, operating under mesophilic conditions that realized biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…39 On the other hand, Prevotella , Caproiciproducens and Ruminiclostridium were found to be beneficial together for the degradation of polysaccharides and protein, such as cellulose and hemicellulose and contribute to the acidification process. 40–42 Taken together, these results suggested that the above-mentioned genera preferred to live in high strength wastewater and were the key degraders in biofilms under anaerobic conditions, which was inconsistent with their highly positive associations with COD loading rate and influent COD concentration as identified by the CCA analysis (Fig. 6a).…”
Section: Resultsmentioning
confidence: 83%
“…39 On the other hand, Prevotella , Caproiciproducens and Ruminiclostridium were found to be beneficial together for the degradation of polysaccharides and protein, such as cellulose and hemicellulose and contribute to the acidification process. 40–42 Taken together, these results suggested that the above-mentioned genera preferred to live in high strength wastewater and were the key degraders in biofilms under anaerobic conditions, which was inconsistent with their highly positive associations with COD loading rate and influent COD concentration as identified by the CCA analysis (Fig. 6a).…”
Section: Resultsmentioning
confidence: 83%
“…Stage-specific bacterial and archaeal populations were found to reside in thermophilic or mesophilic AD bioreactors [ 55 ]. Several metagenomic studies revealed high functional redundancy in AD bioreactors [ 56 ], explained by taxonomic variations under certain changing operational conditions, while biogas production remained relatively stable.…”
Section: Resultsmentioning
confidence: 99%
“…However, no methane usage-related genes have been described in Proteiniphilum genomes, and it is not considered a methanotroph ( Wu et al, 2021 ). Instead, Proteiniphilum has been shown to produce acetate, formate, and multiple volatiles, as well as a variety of extracellular enzymes ( Kabaivanova et al, 2022 ). Similarly, analysis of our previous mica schist-derived Proteiniphilum MAG (OKU04) suggested the genetic potential for a wide enzyme pool and the potential for acetogenesis and nitric oxide reduction in the deep subsurface ( Nuppunen-Puputti et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%